Direct asymmetric synthesis of α-deuterated α-amino acid derivatives from the parent α-amino acids via memory of chirality. Issue 13 (28th March 2018) - Ohtsuki, Haruka; Takashima, Megumi; Furuta, Takumi; Kawabata, Takeo
Graphical abstract: Highlights: Asymmetric α-deuteration of α-amino acids was developed via memory of chirality. α-Deuteration took place in retention of the configuration in 60–98% ee. Parent α-amino acids were employed as a sole source for asymmetric induction. Abstract: A method for asymmeyric α-deuteration of α-amino acid derivatives has been developed by a memory of chirality (MOC) strategy. The α-deuterated α-amino acid derivatives with 88–93% D were obtained in 60–98% ee in retention of the configuration (7 examples). The characterisrtic feature of the present procedure is that asymmeric induction was achieved by employing the parent amino acid derivatives as a sole source of chirality without the use of any external chiral souces.